Aplikasi Data Mining untuk Mencari Pola Asosiasi Tracer Study Menggunakan Algoritma FOLDARM - Lisna zahrotun; Tedy Setiadi; Taufik Mufti Haryadi (Jurnal Nasional Teknologi dan Sistem Informasi, 2018)
A tracer study is an approach that allows higher education institutions to obtain information about possible deficiencies during educational process and learning process and activity planning for improvement. Institute of Student Affairs never do a tracer study data analysis, although tracking of graduate student has been periodically using web-based application but the previous data is still in old format. Tracer study process is only once time in order to completed   accreditation requirement for department. In this research we will focus in developing the application using FOLDARM method for student tracer study. Application is created using the CI Framework programming language with   Mysql as backend database. The test is done using lift ratio method. The result show, association of the patterns are counted by 3, 24% support and confident 45% and it that meet the criteria. By using lift ratio test, the pattern that has the strongest relationship is if the waiting period in finding a job is 3- 5,9 month and first salary is below Rp. 1,572,200,-  and IPK is between 2.75 - 3.50 and graduation age is between 15-24 years old.